2012
DOI: 10.2527/jas.2011-4567
|View full text |Cite
|
Sign up to set email alerts
|

Wet distillers grains plus solubles concentration in steam-flaked-corn-based diets: Effects on feedlot cattle performance, carcass characteristics, nutrient digestibility, and ruminal fermentation characteristics1

Abstract: Two experiments were conducted to determine the effects of wet distillers grain plus solubles (WDG; <15% sorghum grain) concentration in steam-flaked corn (SFC) diets on feedlot performance, carcass characteristics, ruminal fermentation, and diet digestibility. In Exp. 1, six hundred crossbred steers (364 ± 35 kg of BW) were used in a randomized complete block design with 8 replications/treatment. Dietary treatments consisted of a dry-rolled corn (DRC) control diet without WDG, a SFC control without WDG, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 44 publications
8
37
1
1
Order By: Relevance
“…Notwithstanding decreased starch intake and decreased ruminal OM digestion (Table 3), ruminal pH at 4 h after feeding was unaffected (P = 0.80) by level of DDGS substitution for SF corn. This response is consistent with several studies evaluating substitution of DDGS for corn in fi nishing diets (Ham et al, 1994;May et al, 2009May et al, , 2010Uwituze et al, 2010;Luebbe et al, 2011). In some cases (Peter et al, 2000;Leupp et al, 2009b), however, partial replacement of corn with distillers grains increased ruminal pH.…”
Section: Methodssupporting
confidence: 90%
“…Notwithstanding decreased starch intake and decreased ruminal OM digestion (Table 3), ruminal pH at 4 h after feeding was unaffected (P = 0.80) by level of DDGS substitution for SF corn. This response is consistent with several studies evaluating substitution of DDGS for corn in fi nishing diets (Ham et al, 1994;May et al, 2009May et al, , 2010Uwituze et al, 2010;Luebbe et al, 2011). In some cases (Peter et al, 2000;Leupp et al, 2009b), however, partial replacement of corn with distillers grains increased ruminal pH.…”
Section: Methodssupporting
confidence: 90%
“…Generally, increasing DDGS levels in concentrate feed mixture showed significantly (P<0.05) higher digestibility coefficients for all nutrients except for EE digestibility and higher nutritive values of the rations when expressed as TDN, DCP or DE. Data were agreement with those obtained by Walter et al, (2012), Felix et al, (2012), Luebbe et al, (2012) and Leupp et al, (2009).…”
Section: Effect Of Using Different Levels Of Ddgs On Feed Intake Digsupporting
confidence: 92%
“…The high potential of the nutritional value of DDGS can be useful for replacing dry-rolled (DR) or steam-flaked corn in growing-finishing diets of beef cattle (Klopfenstein, 2008). However, it appeared that the feed value of distillers grains may vary by level of inclusion (Uwituze et al, 2010) and by the type of processing (DR or steam-flaked) of the corn grain that is replaced (May et al, 2009; Luebbe et al, 2012). The optimal responses (daily weight gain and feed efficiency) in feedlot cattle when DDGS has replaced corn grain in finishing diets have been observed with moderate levels (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal responses (daily weight gain and feed efficiency) in feedlot cattle when DDGS has replaced corn grain in finishing diets have been observed with moderate levels (i.e. 20%) of DDGS inclusion as a replacement of steam-flaked grain (May et al, 2009; Uwituze et al, 2010; Luebbe et al, 2012). Leupp et al (2009) have reported that replacing DR corn with up to 60% DDGS in 70% concentrate diets resulted in no adverse effects on total tract OM digestion in steers, although ruminal OM digestion decreased and microbial production efficiency increased with increasing DDGS.…”
Section: Introductionmentioning
confidence: 99%